The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/mds.26477
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Alpha‐Synuclein: Relevance to Parkinson's Disease and Related Synucleopathies

Abstract: Evidence from human postmortem material, transgenic mice, and cellular/animal models of PD link alpha-synuclein accumulation to alterations in the autophagy lysosomal pathway. Conversely, alpha-synuclein mutations related to PD pathogenesis, as well as post-translational modifications of the wild-type protein, result in the generation of aberrant species that may impair further the function of the autophagy lysosomal pathway, thus generating a vicious cycle leading to neuronal death. Moreover, PD-linked mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
170
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(190 citation statements)
references
References 149 publications
3
170
0
7
Order By: Relevance
“…Numerous studies have indicated that autophagy is involved in the pathological changes observed in PD (2527). However, the explicit role of autophagy in iron-induced pathology is still uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have indicated that autophagy is involved in the pathological changes observed in PD (2527). However, the explicit role of autophagy in iron-induced pathology is still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, growing evidence has indicated an intimate relationship between autophagy and PD, showing that autophagy dysregulation may play a critical role in the development of PD. Aggregates of α-synuclein are mainly degraded via the autophagy pathway (2527), including macroautophagy and CMA pathways (24). The autophagy signaling pathway has been reported to be disrupted in PD (28).…”
Section: Introductionmentioning
confidence: 99%
“…Defects in autophagy and lysosomal function have both been observed in PD (Lynch-Day et al, 2012; Nixon, 2013; Xilouri et al, 2016). One of the strongest links between lysosomal function and PD is found with the enzyme β-glucocerebrosidase (GBA) (Table 1, Fig.…”
Section: Intracellular Ca2+ Stores and Their Deregulation In Pdmentioning
confidence: 99%
“…An additional interesting hub gene in this module is Bloc1s1 . Bloc1s1 is a component of the BLOC-1 complex, which is involved in the biogenesis of lysosome-related organelle, suggesting a potential influence on lysosomal degradation of aggregates or dysfunctional organelles, both of which have been strongly implicated in synucleinopathies [17, 34, 50, 106]. In addition, the BLOC-1 complex is also involved in the negative regulation of aerobic respiration through mitochondrial protein lysine-acetylation [88, 89].…”
Section: Resultsmentioning
confidence: 99%